2006
DOI: 10.1002/pssb.200541269
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray absorption and luminescence properties of metallic copper nanoparticles embedded in a glass matrix

Abstract: A new method of ion-exchange between raw compounds containing copper oxide and alkali glasses has been used to grow copper nanoparticles within a glass matrix, forming a metal-glass nanocomposite that is the structure on which both ancient and modern lustre glazes are based. When excited by X-rays at 300 K, two dominant emission bands appear in the material in the visible region, peaking at 2.60 eV and 1.98 eV. Synchrotron radiation methods are deployed that enables the luminescence and structural properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…In particular, extended x-ray absorption fine structure ͑EXAFS͒ and transmission electron microscopy ͑TEM͒ analysis of a luster layer prepared following the same thermal protocol on the lead free glaze, thus equivalent to j6, has been recently performed. 25 The size of the nanoparticles fully matches the size obtained by SR-Micro-XRD; the luster layer has a higher density of nanoparticles in a sublayer of about 800 nm thickness and has a copper free outer layer of about 50 nm. EXAFS data determined 77± 4% copper metal, with the remainder as the cuprite.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…In particular, extended x-ray absorption fine structure ͑EXAFS͒ and transmission electron microscopy ͑TEM͒ analysis of a luster layer prepared following the same thermal protocol on the lead free glaze, thus equivalent to j6, has been recently performed. 25 The size of the nanoparticles fully matches the size obtained by SR-Micro-XRD; the luster layer has a higher density of nanoparticles in a sublayer of about 800 nm thickness and has a copper free outer layer of about 50 nm. EXAFS data determined 77± 4% copper metal, with the remainder as the cuprite.…”
Section: Resultssupporting
confidence: 73%
“…EXAFS data for a lead free glaze luster ͑similar to j6͒, a luster layer produced following the same thermal protocol 25 showed that 77± 4% of the copper was in metallic state while the rest was a cuprite. However, it is also well known that due to the fact that the reducing process results from the penetration of the reducing atmosphere into the luster layer, the outer surface is always more reduced than the inner region of the luster layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 In fact, red non-coppery luster layers produced on a lead free glaze were thick (800 nm) and formed by 10 nm copper nanoparticles. 23 On the contrary, the coppery luster layers produced over PbO containing glazes following the same protocol were thin (150 nm) 17 and contained large (50 nm size) and small (a few nanometers size) copper nanoparticles. Therefore, it was not possible to elucidate which of the factors or combination of the factors was responsible of the metallic appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, UV-visible absorption spectra of metal nanoparticles are often displayed as a broad spectrum originated from the conduction electron transitions with exceptionally degenerate states. This is in marked contrast with absorption properties of the valence electrons of metal nanoparticles such as luminescence (Drachev et al, 2004) and fluorescence (Roque et al, 2006), where the quantized states are readily observed due to welldefined energy gap between two occupied energy states. In metal nanoparticles, the electron-hole interaction is screened off and the conduction electrons behave as nearly free.…”
Section: Introductionmentioning
confidence: 81%